DISPARITAS PUTUSAN HAKIM DALAM MENJATUHKAN PIDANA PADA TINDAK PIDANA NARKOTIKA - Encep Henry; Andhi Wibowo (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Disparity of punishment is often associated with the independence of judges because the punishment model set forth in the Criminal Code only formulates maximum penal sanctions only, in addition because u ndangjudicial power also regulates that The judge must also consider the good and evil nature of the defendant. The disparity of the decision of the judge also occurred in the District Court of Class IA Padang whichexamined and decided on the case of narcotics crime with the same panel of judges and the indictment of the same article but the decision given to the defendant was different. With the occurrence of criminal disparity without any explanation to the general public then the impact of the emergence of a sense of injustice in the convicted parties themselves and the people who do not know the background of the criminal provision.